Uji Validitas dan Reliabilitas Multicultural Attitude Scale Questionnaire (MASQUE) Versi Indonesia dengan Model Rasch - Livia Tanujaya; Ananta Yudiarso (Universitas Kristen Maranatha, 2023)
Indonesia is a multicultural country that refers to the diversity of tribes, races, religions and beliefs. This study aims to enrich the development findings by providing psychometric information on the Munroe Multicultural Attitude Scale Questionnaire (MASQUE) using the Model Rasch perspective. This also introduces the application of the Model Rasch in analyzing the validity of the Munroe Multicultural Attitude Scale Questionnaire (MASQUE). This instrument has three aspects, namely (1) Knowledge, (2) Concern, and (3) Action and has a total of 18 items. Respondents used in this study were 210 students who were taken using simple random sampling method. The results of data analysis using the Model Rasch show that the Indonesian version of the MASQUE instrument has items that are fit and have quite a variety of item difficulty levels, but adjustments need to be made in order to facilitate a more varied personability and items that are spread out in more appropriate aspects.